A Study on Students’ Perceptions Toward Their Teacher’s Code Switching in Teaching English at MTs Hidayah Ma’arifiyah Pangkalan Kerinci (Bedelau: Journal of Education and Learning, 2022)
This study is a survey research design aiming at investigating students' perceptions of their teachers' code switching in English teaching. The population of the research is the eighth-grade students at MTs Hidayah Ma'arifiyah Pangkalan Kerinci totaling 112 students. Then, by using the convenience sampling technique, the researchers took 53 students as the study sample. In collecting the data about students' perceptions, the researchers adapted a perception questionnaire from Fauzanah and Sitti (2019), and Catabay (2016). Hence, researchers used SPSS software to analyze the data. The results of the statistical analysis show that students' perceptions of their teacher' code switching in teaching English are positive with a 63% response score in the Likert scale questionnaire administered. Furthermore, the researchers also reveal that the students felt the code switching made by their teachers helped them learn English better in some points such as it facilitates students with easier understanding of the difficult concept, vocabulary, and, ideas, as well as arouses students' motivation and confidence.